UV-sensitive syndrome: Whole exome sequencing identified a nonsense mutation in the gene UVSSA in two consanguineous pedigrees from Pakistan. Issue 3 (September 2019) - Ijaz, Ambreen; Wolf, Sabrina; Mandukhail, Safur Rehman; Basit, Sulman; Betz, Regina C.; Wali, Abdul
Highlights: We report nine UVSS cases from Pakistani with a novel nonsense mutation in UVSSA . This is the first report of UVSS in the Pakistani population. The identified mutation is the fourth report of a pathogenic mutation in UVSSA . The here described nonsense mutation leads to a truncated UVSSA protein. This mutation results in a mislocalisation of UVSSA from the nucleus to the cytoplasm. Abstract: Background: UV-sensitive syndrome (UV S S) is a rare autosomal recessive genodermatosis characterised by photosensitivity, and hyperpigmentation, freckling, and dryness of sun exposed areas. In contrast to other photosensitivity disorders, affected patients show no predisposition to cutaneous melanoma or neurological dysfunction. UV S S results from a defect in the transcription-coupled nucleotide excision repair (TC-NER) mechanism. UV S S can be caused by mutations in the genes ERCC8, ERCC6, and UVSSA . Objective: To determine the underlying genetic cause of UV S S and its functional consequences in nine members of two large, unrelated consanguineous pedigrees from Pakistan. Methods: Genomic DNA from one affected member of each family was subjected to whole exome sequencing. The identified mutation was then validated via Sanger sequencing using samples from all available family members. Molecular cloning and mammalian cell cultures were used for the translation and localisation of wild type (WT) and mutant constructs. Results: A novel homozygous nonsense mutation, (c.1040 G > A[ p.(Trp347*)]), was detected in exon 6 of the UVSSA gene in both families. Sanger sequencing revealed co-segregation of the nonsense mutation with the UV S S phenotype. Immunoblotting revealed the anticipated 81 kDa band for the WT construct, and a truncated protein of around 39 kDa for the mutant. In mutant samples, immunofluorescence revealed mislocalisation of UVSSA from the nucleus to the cytoplasm. Conclusions: This is the first report of UV S S in the Pakistani population and the fourth report of a disease-causing mutation in UVSSA . The study broadens the UVSSA mutational spectrum, and contributes to functional understanding of truncated UVSSA proteins.